História da cachaça em Abaetetuba: o auge e o declínio dos engenhos - PEREIRA, Marília da Silva (2024)
Such research will seek to develop a study on the peak and decline of the mills in the city of Abaetetuba in Pará Taking as an object of the same, the only remaining mill's heyday of spirits in the City - Skill Pacheco - in the decades since 40 and 50, there were about sixty (60) of them. And to fuel this study fieldwork seeking enrollment in locus, through interviews, field reports, analyzes of reality, photographs, among others was developed. Abaetetuba enjoyed a period of great economic importance for Tocantina region, becoming the leading exporter of rum. This product was in the twentieth century, the main base of the economic County and contributed to the development in the period. This study aims to research this golden period and the factors that led to the decline of the main product of abaetetubense-based economy.